2021
DOI: 10.1111/gwao.12604
|View full text |Cite
|
Sign up to set email alerts
|

Pandelivery1: Reflections on black delivery app workers experiences during COVID‐19 in Brazil

Abstract: This article reflects on how the COVID-19 pandemic has affected the lives of black men who work as app delivery workers in Brazil. The coronavirus spread affected the demand for delivery services in the last mile delivery without necessarily improving working conditions. We highlight not only how structural racism shapes the daily lives of these workers, revealing experiences of inequality, marginalization, suffering, but also their resistance strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
0
13
0
2
Order By: Relevance
“…Huang, 2022b; Lee, 2018; Moore, 2018; Sun, 2019). In so doing, algorithm‐based technology contributes to upholding existing socio‐economic class hierarchies (Cant, 2019; Cant & Woodcock, 2020; Lage & Rodrigues, 2021; Lee, 2018; van Doorn et al, 2020).…”
Section: Power Of Algorithms In On‐demand Food Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Huang, 2022b; Lee, 2018; Moore, 2018; Sun, 2019). In so doing, algorithm‐based technology contributes to upholding existing socio‐economic class hierarchies (Cant, 2019; Cant & Woodcock, 2020; Lage & Rodrigues, 2021; Lee, 2018; van Doorn et al, 2020).…”
Section: Power Of Algorithms In On‐demand Food Deliverymentioning
confidence: 99%
“…Lee, 2018; Marrone & Peterlongo, 2020). Studying black couriers in Brazil, Lage and Rodrigues (2021, pp. 438–439) found that their pay has dropped during the COVID‐19 pandemic despite working on average 9–12 h per day while “being perceived or identified as a criminal because of his appearance.” What is unique about the platform economy, Stark and Pais (2021, p. 47) tell us, is how the platform owners “co‐opt the behavior of providers and users, enrolling them in the practices of algorithmic management without managerial authority having been delegated to them.”…”
Section: Power Of Algorithms In On‐demand Food Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…In organizational studies, the relevance and emergence of understanding the topic are seen in full theoretical reflections and recent literature reviews that address algorithmically mediated management and its potential impacts (Kellogg et al, 2020;Trittin-Ulbrich et al, 2020;Brevini & Pasquale, 2020). Among the consequences discussed, studies related to algorithms and organizations reveal the possibility that data management interferes in various aspects of organizational dynamics, such as the formation and relationships of social groups in the organizational environment (Vaast, 2020;Lage & Rodrigues, 2020), fantasies of digitization in the workplace (Hensmans, 2020), loss of privacy (Anteby & Chan, 2018;Rosenblat & Stark, 2016;Woodcock, 2020); algorithmic control of work Curchod et al, 2019;Faraj et al, 2018), and workers' habits (Elmholdt et al, 2020) such as algo activity or workers' activism movements (Kellogg et al, 2020;Mercea & Yilmaz, 2018;Petriglieri et al, 2019;Mercea & Yilmaz, 2018;Etter & Albu, 2020;Birch, 2020;Petriglieri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, efforts to investigate the relationship between technology and organizations are mostly advancing in the sociology of work (Abilio, 2020;Filgueiras & Antunes, 2020;Grohmann & Qiu, n.d.), and communication (Bruno et al, 2018;Silva & Birhane, 2020). In the area of administration, some recent studies have been limited to addressing the phenomenon of uberization (Insardi & Lorenzo, 2019;Kalil & Lopes, 2018;Serrano & Baldanza, 2017;Valente et al, 2019;Vianna et al, 2018), with a few adopting critical perspectives (Lage & Rodrigues, 2020;André et al, 2019;Franco & Ferraz, 2019;Guimarães Pinho, 2009;Antonio & Caetano, 2006;Fernandes & Raduenz, 2020;Oliveira Abensur, 2007;Vianna & Meneghetti, 2020).…”
Section: Introductionmentioning
confidence: 99%